GAMBARAN PENATALAKSANAAN BAYI BARU LAHIR YANG MENGALAMI ASFIKSIA NEONATORUM DI RUMAH SAKIT UMUM DAERAH DR.H.SOEWONDO KABUPATEN KENDAL - Mimi Ruspita; Heny Rosiana (Midwifery Care Journal, 2020)
Asphyxia neonatorum is a newborn baby emergency because of  breathing difficulties that can continue to cause various complications. Asphyxia is most common in the period immediately after the baby is born. It is estimated that one third of babies who need resuscitation do not show danger signs, therefore very important for midwives to be able to carry out simple and effective neonatal resuscitation. The purpose of this search is to know the description of the management of neonatal asphyxia by type and SOP in RSUD DR. H. Soewondo Kendal.This research is a descriptive study using a survey approach. The method of collecting data by observing using a checklist and SOP checklist for management asphyxia neonatorum which is then processed using Univariate analysis. The results showed that the management of neonatal asphyxia in 42 infants, all (100%) were resuscitated, 9 infants (21,4%) had VTP and 4 infants (9,5%) had chest compressions. While of 42 treatments that have been carried out there are actions that are not in accordance with the SOP. The results showed that the management of newborns who had neonatal asphyxia had not been carried out according to the SOP. So it is recommended especially for midwives to have awarness of the importance of managing neonatal asphyxia in accordance with SOP.